35. Association of robot-assisted rehabilitation and non-invasive brain stimulation to improve upper limb function in chronic stroke patients. Issue 12 (December 2017) - Capone, F.; Di Pino, G.; Pellegrino, G.; Florio, L.; Zollo, L.; Simonetti, D.; Ranieri, F.; Brunelli, N.; Corbetto, M.; Miccinilli, S.; Bravi, M.; Milighetti, S.; et al.
Abstract : Previous studies suggested that both robotic rehabilitation and non-invasive brain stimulation could produce improvement in chronic stroke patients. It is still unknown whether their combination can produce synergistic effects. We designed a proof-of-principle, double-blinded, semi-randomized, sham-controlled trial to assess the safety and efficacy of this combination. Twenty severe upper limb-impaired chronic stroke patients were randomized to robot-assisted therapy associated with real or sham cTBS, delivered for 10 working days. Eight real and nine sham patients completed the study. Change in Fugl-Meyer was chosen as primary outcome, while changes in several quantitative indicators of motor performance extracted by the robot as secondary outcomes. The treatment was well-tolerated and there were no adverse events. All patients achieved a small, but significant, Fugl-Meyer improvement. The difference between the real and the sham cTBS groups was not significant. Among several secondary end points, only the Success Rate improved more in the real than in the sham cTBS group. This study shows that a short intensive robot-assisted rehabilitation produces a slight improvement in severe upper-limb impaired, even years after the stroke. The association with homeostatic metaplasticity-promoting non-invasive brain stimulation does not augment the clinical gain in patients with severe stroke.